Red Hawk Rocketry Boosted Dart - Izewski, James Michael (Proceedings of the Wisconsin Space Conference, 2016)
As part of the Wisconsin Space Grant Consortium competition, Red Hawk Rocketry built a rocket for the Collegiate Rocket Launch Competitionâ€™s non-engineering contest. The launch went well, albeit a little unstable, veering in the direction of the wind. This was unexpected since within our RockSim files, our rocket was considerably over stable, so it should have turned into the wind. Its apogee was around 1000 feet due to the fact that our rocket was rather massive compared to other teams. However, because of its low apogee, we were able to easily locate and retrieve the rocket upon landing, as intended. Finally, all three aspects of the challenge were completed successfully; the dart separated, we were able to access mid-flight rotation data from our gyroscope, and we obtained on board, down looking video during the flight. Â 